Statistical analysis of a survey about diffusion of binge drinking and drunkorexia among students in Palermo - Fabio Venturella; Giulia Cancellieri; Marco Giammanco; Anastasia Valentina Liga (Journal of Biological Research, 2018)
Youth alcohol consumption is a major global public health concern. Previous reviews have concluded that exposure to alcohol marketing was associated with drinking initiation and higher alcohol consumption among youth. From January to May 2017, a survey has been conducted through administration of questionnaires about the diffusion of Binge Drinking and Drunkorexia among the students of Palermo. Test was administered, during school time, to 2331 students between the ages of 13 and 20. Regarding the analysis of the questionnaires, 97,8% of student declares to have drunk at least once: their first taste of alcoholic drink happens at the age of thirteen/fourteen. They prefer to drink at the disco or pub (48% disco; 22% pub) on Friday and Saturday evening (92%). 52% of students also declare to associate alcohol to cigarette smoking. Another important statistic is that 736 girls and 61 boys declare to prefer to restrict food intake in order to consume greater quantities of alcohol and to avoid weight gain. In order to evaluate youth alcohol consumption in a different contest, it was created an online survey thanks to Google forms. This study involved 500 young people from Palermo between the ages of 19 and 30. The extrapolation of data confirmed the same results of the questionnaires on paper. In this test, however, it was also evaluated the spreading of drink-driving (68,5%). The present survey suggests that there is an expansion of such practices in young population. In conclusion, it appears necessary to adopt measures of information and prevention to reduce territorial diffusion.